DETERMINASI FAKTOR-FAKTOR YANG MEMPENGARUHI KETERSEDIAAN PANGAN RUMAH TANGGA PETANI PADI DI DESA KALIBENING KABUPATEN MUSI RAWAS - Sysmita, Virlianda; Wildayana, Elisa; Yunita, Yunita (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
The availability of food in their households, can be affected by various factors such as certain land conditions, price fluctuations, government policies, and the impact of climate change. The objectives of this study are Analyzing factors that affect food availability on food availability in rice farmer households in Musi Rawas Regency. This research was conducted in Musi Rawas Regency, Tugumulyo District in Kali Bening Village at December 2024. The research methods used are the survey method and the method of drawing examples of the simple random sample method. The data used are primary and secondary data. The results of this study are factors that significantly affect the availability of staple food (rice) in Kali Bening Village, Tugu Mulyo District, Musi Rawas Regency are the Number of Dependents, Land Area and Expenditure, where the Number of Dependents and Land Area are positively affected while expenditure is negatively affected.